UPAYA MENINGKATKAN MINAT BELAJAR SISWA SD MELALUI PROGRAM BIMBEL DI DUSUN KRANDEGAN DESA SUKOMAKMUR - Milatina Qurota A'yunina; Milna Wafirah; Laili Syarifah; Prawidya Lestari (khidmatan, 2025)
Interest in learning involves a person's full involvement by pouring all their thoughts and attention into acquiring knowledge and achieving an understanding of the knowledge they require. The student's obligation is to keep learning in the learning process and due to factors of minimal interest in learning such as reading, lack of knowledge in learning computers. This is very influential for students, students feel bored and have difficulty dealing with the learning process, especially learning IT and can cause students to have low interest in learning. The aim of this service is to make students learn together while playing by increasing students' interest in learning through a tutoring program. The method in this research is the Participatory Action Research (PAR) method, namely action research and participation. With the intelligence that each student has, motivation from teachers and parents, student independence in learning, how teachers teach, praise if students can complete assignments correctly, how to give rewards and punishments to students, with some of these innovations it will be possible for students to increase students' interest in learning.